Waste materials utilization in 3D printable concrete for sustainable construction applications: a review - Mohammad Irshidat (16494152) (2024)
Three dimensionally printed concrete (3DPC) is an interesting topic that has attracted increasing attention during the last few years. This paper offers a comprehensive review of the utilization of waste materials in 3DPC. The literature on the different waste materials that have been utilized in 3DPC, such as silica fume, fly ash, recycled sand, waste glass, municipal incineration ash, ground granulated blast furnace slag, and steel slag, are reviewed. The influence of these waste materials on the main parameters of 3D printing of concrete such as the buildability, extrudability, and open time are discussed. In addition, the paper addressed the effect of these wastes on the mechanical strengths of the printed concrete. This paper finds that merging the technology of 3D printing of concrete with the usage waste materials will revolutionize the construction industry by addressing the challenges in meeting the required strength parameters of concrete using 3D printing technology and at the same time making construction process more economically and environmentally viable. Finally, to improve the efficiency of this emerging construction technique, authors recommend using combination of different waste materials together, taking into consideration using some additives to balance out the negative effects of waste materials on other parameters. Other Information Published in: Emergent Materials License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s42247-024-00942-4